Language anxiety and the online learner - Russell, Victoria (Foreign language annals, 2020)
Foreign language classroom anxiety is a construct that has been investigated since the 1980s, yet few studies have examined language anxiety in the context of the online learning environment. In this literature review, the following guiding questions were examined: (a) What is foreign language classroom anxiety? (b) What are the research findings on language anxiety among online learners? (c) What can instructors do to help alleviate their online students' perceived levels of language anxiety? In addition to an exploration of the guiding questions, the Foreign Language Classroom Anxiety Scale, which was developed by Horwitz, Horwitz, and Cope (1986), is described in detail as well as how language educators can use it as a tool in their own classrooms to measure their students' perceived language anxiety levels. The pedagogical implications include recommended techniques and interventions for helping online language learners feel less isolated, less anxious, and more connected to their teacher and to their peers. Given the large number of students who are currently engaged in online or remote language learning due to COVID‐19, it is important to consider how affective factors, such as anxiety, can impede learning outcomes. Furthermore, language educators and their students were required to transition rapidly to the online environment without sufficient time or preparation for it, which is an additional cause of stress for both students and instructors alike. The article concludes with suggestions for future research on online language anxiety. The Challenge K‐16 language learners are currently working under conditions of considerable stress since being forced into remote learning due to the global pandemic. Moreover, students who learn language online may experience significant levels of perceived language anxiety and/or anxiety related to their use of new instructional technologies and platforms. Students are likely also experiencing higher levels of general anxiety related to the pandemic and their home situation. How can language educators address these concerns? This article provides some research‐based pedagogical techniques and interventions to help instructors to do so.